Comparison of heart rate variability before and after a table tennis match - Picabea, J. N.; Cámara, J.; Nakamura, F. Y.; Yanci, J. (Journal of Human Kinetics, 2021)
The aim of this study was to compare heart rate variability indices before and after a table tennis match. Sixteen males (21.86 ± 8.34 yr, 1.73 ± 0.08 m, 64.09 ± 13.39 kg and 21.46 ± 4.38 kg/m2) were evaluated in 21 matches, before and after the match. We observed that in time domain analysis, Mean RR, SDNN, LnRMSSD and pNN50 after match values were significantly lower than before match values (p < 0.01 or p < 0.05), while Mean HR, Min HR and Max HR values were higher (p < 0.01) after than before the match, with no significant differences (p > 0.05) in STD HR. Meanwhile, frequency domain analysis showed LF Power (log), HF Power (log) and HF Power (in normalized units) after match values significantly lower than before match values (p < 0.01 or p < 0.05), while LF/HF value was higher after the match (p < 0.01), with no significant differences (p > 0.05) in LF Power (ms2), LF Power (in normalized units) and HF Power (ms2) values. Non-linear analysis showed SD1 and SD2 POST values significantly lower than PRE values (p < 0.05), while no significant differences were observed in SD2/SD1 value between POST and PRE analysis. As conclusion, due to the physiological strain of the table tennis match, changes were observed in heart rate variability values, suggesting an increase of sympathetic influence and a reduction of the parasympathetic influence.